Surface and interface chemistry in metal‐free electrocatalysts for electrochemical CO2 reduction. Issue 1 (2nd February 2022) - Zhang, Wei; Jia, Baohua; Liu, Xue; Ma, Tianyi
Abstract: The electrochemical reduction of carbon dioxide (CO2 ) into value‐added fuels and chemicals presents a sustainable route to alleviate CO2 emissions, promote carbon‐neutral cycles and reduce the dependence on fossil fuels. Considering the thermodynamic stability of the CO2 molecule and sluggish reaction kinetics, it is still a challenge to design highly efficient electrocatalysts for the CO2 reduction reaction (CO2 RR). It has been found that the surface and interface chemistry of electrocatalysts can modulate the electronic structure and increase the active sites, which is favorable for CO2 adsorption, electron transfer, mass transport, and optimizing adsorption strength of reaction intermediates. However, the effect of surface and interface chemistry on metal‐free electrocatalysts (MFEs) for CO2 RR has not been comprehensively reviewed. Herein, we discuss the importance of the surface and interface chemistry on MFEs for improving the electrochemical CO2 RR performance based on thermodynamic and kinetic views. The fundamentals and challenges of CO2 RR are firstly presented. Then, the recent advances of the surface and interface chemistry in improving reaction rate and overcoming reaction constraints are reviewed from regulating electronic structure, active sites, electron transfer, mass transport, and intermediate binding energy. Finally, the research challenges and prospects are proposed to suggest the future designs of advanced MFEs in CO2 RR. Abstract : The surface and interface chemistry of metal‐free electrocatalysts from regulating electronic structure, electron transfer, mass transport, stabilizing reaction intermediates, and exposure active sites to adjust reaction kinetics, reaction pathways and performance of electrochemical reduction CO2 were reviewed.